Barriers to medication adherence among adolescents and young adults with cancer. Issue 3 (5th January 2023) - McGrady, Meghan E.; Ketterl, Tyler G.; Norris, Robin E.; Perentesis, John P.; Pettee, Daniel; Mara, Constance A.; Breen, Gabriella; Pai, Ahna L. H.
Abstract: Background: Adherence promotion is a critical component of adolescent and young adult (AYA) cancer care, but predictors of nonadherence that could be targeted in intervention efforts remain largely unknown. The purpose of this multi‐site longitudinal observational study was to examine the relationship between barriers and medication adherence among AYAs with cancer. Procedure: Sixty‐five AYAs (ages 15–24 years; mean age = 18.97 years, SD = 2.51; M mean time since diagnosis = 1.42 years, SD = 1.95) with newly diagnosed or relapsed cancer completed self‐report measures of barriers and adherence at quarterly study visits and used an electronic adherence monitoring device for 12 months. Longitudinal mixed effects models were used to examine our primary hypothesis that greater barriers are related to lower adherence over time. Descriptive statistics were used to explore our secondary aim of describing the frequency and patterns of barriers endorsed by AYAs with cancer. Results: After controlling for covariates (time, medication type, race, ethnicity, diagnosis, time since diagnosis), a greater number of barriers was associated with lower electronically monitored ( β = −5.99, p = .005) and self‐reported ( β = −1.92, p < .001) adherence. The specific barriers endorsed by AYAs differed across participants, and the majority of AYAs endorsed an entirely different pattern of barriers than any other AYA in the study. Conclusion: Barriers are associated with nonadherence and may be a promising target for intervention. Individual variability across barriers, however, suggests that tailoring may be necessary, and a promising next step is to explore personalized approaches to adherence promotion.